2013
DOI: 10.1088/0004-637x/772/1/60
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Origin of the [O I] Low-Velocity Component From T Tauri Stars

Abstract: The formation time, masses, and location of planets are strongly impacted by the physical mechanisms that disperse protoplanetary disks and the timescale over which protoplanetary material is cleared out. Accretion of matter onto the central star, protostellar winds/jets, magnetic disk winds, and photoevaporative winds operate concurrently. Hence, disentangling their relative contribution to disk dispersal requires identifying diagnostics that trace different star-disk environments. Here, we analyze the low-ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
154
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 98 publications
(172 citation statements)
references
References 89 publications
(120 reference statements)
16
154
2
Order By: Relevance
“…For EUV-heated, fully ionized winds, data is consistent with mass loss rates of ∼ 10 −10 M ⊙ yr −1 , while partly neutral X-ray heated gas implies higher rates ∼ 10 −9 to 10 −8 M ⊙ yr −1 . Other low velocity wind tracers such as [OI] forbidden line emission and CO rovibrational emission are more difficult to interpret with contributions from multiple components (Rigliaco et al 2013). For a more in-depth discussion, see Alexander et al (2014).…”
Section: Gas Diagnostics Of Photoevaporationmentioning
confidence: 99%
“…For EUV-heated, fully ionized winds, data is consistent with mass loss rates of ∼ 10 −10 M ⊙ yr −1 , while partly neutral X-ray heated gas implies higher rates ∼ 10 −9 to 10 −8 M ⊙ yr −1 . Other low velocity wind tracers such as [OI] forbidden line emission and CO rovibrational emission are more difficult to interpret with contributions from multiple components (Rigliaco et al 2013). For a more in-depth discussion, see Alexander et al (2014).…”
Section: Gas Diagnostics Of Photoevaporationmentioning
confidence: 99%
“…It could be emitted at the base of a magnetically driven disk wind, as suggested by Hartigan et al (1995) for the O  lines, but it can also be a tracer of a photoevaporative disk wind, as shown by, e.g., Pascucci & Sterzik (2009) for the LVC of the Ne  mid-IR emission lines. Lately, Rigliaco et al (2013) have shown that the LVC O  lines could also have multiple components, with one component tracing gas in Keplerian rotation and another component tracing a photoevaporative wind. Acke et al (2005) find that in Herbig Ae/Be stars, the [O ] 630.03 nm emission could come from the disk surface layers.…”
Section: Introductionmentioning
confidence: 99%
“…Star-disk interaction processes can be studied observationally through the strong signatures they introduce in the spectra of YSOs. Accretion shocks give rise to continuum excess emission in the UV (e.g., Valenti et al 1993;Gullbring et al 1998Gullbring et al , 2000Calvet et al 2000) and the prominent emission of permitted lines across the whole spectrum (e.g., Muzerolle et al 1998aMuzerolle et al ,b,c, 2003Natta et al 2004), while winds are traced by various forbidden emission lines (e.g., Hartigan et al 1995;Rigliaco et al 2013;Natta et al 2014). In recent years, new instruments have provided the possibility of studying these processes simultaneously in large samples of objects.…”
Section: Introductionmentioning
confidence: 99%